Cell-free hemoglobin mediated oxidative stress is associated with acute kidney injury and renal replacement therapy in severe falciparum malaria: an observational study - Plewes, Katherine (2017)
Background: Intravascular hemolysis is an intrinsic feature of severe malaria pathophysiology but the pathogenic role of cell-free hemoglobin-mediated oxidative stress in severe malaria associated acute kidney injury (AKI) is unknown. Methods: As part of a prospective observational study, enrolment plasma cell-free hemoglobin (CFH), lipid peroxidation markers (F2-isoprostanes (F2-IsoPs) and isofurans (IsoFs)), red cell deformability, and serum creatinine were quantified in Bangladeshi patients with severe falciparum malaria (n = 107), uncomplicated malaria (n = 80) and sepsis (n = 28). The relationships between these indices and kidney function and clinical outcomes were examined. Results: AKI was diagnosed at enrolment in 58% (62/107) of consecutive patients with severe malaria, defined by an increase in creatinine ≥1.5 times expected baseline. Severe malaria patients with AKI had significantly higher plasma cell-free hemoglobin (geometric mean CFH: 8.8 μM; 95% CI, 6.2–12.3 μM), F2-isoprostane (56.7 pg/ml; 95% CI, 45.3–71.0 pg/ml) and isofuran (109.2 pg/ml; 95% CI, 85.1–140.1 pg/ml) concentrations on enrolment compared to those without AKI (CFH: 5.1 μM; 95% CI, 4.0–6.6 μM; P = 0.018; F2-IsoPs: 27.8 pg/ml; 95% CI, 23.7–32.7 pg/ml; P < 0.001; IsoFs: 41.7 pg/ml; 95% CI, 30.2–57.6 pg/ml; P < 0.001). Cell-free hemoglobin correlated with markers of hemolysis, parasite burden (P. falciparum histidine rich protein 2 (PfHRP2)), and F2-IsoPs. Plasma F2-IsoPs and IsoFs inversely correlated with pH, positively correlated with creatinine, PfHRP2 and fractional excretion of sodium, and were higher in patients later requiring hemodialysis. Plasma F2-IsoP concentrations also inversely correlated with red cell deformability and were higher in fatal cases. Mixed effects modeling including an interaction term for CFH and time showed that F2-IsoPs, IsoFs, PfHRP2, CFH, and red cell rigidity were independently associated with increasing creatinine over 72 h. Multivariable logistic regression showed that admission F2-IsoPs, IsoFs and red cell deformability were associated with the need for subsequent hemodialysis. Conclusions: Cell-free hemoglobin and lipid peroxidation are associated with acute kidney injury and disease severity in falciparum malaria, suggesting a pathophysiological role in renal tubular injury. Evaluation of adjunctive therapies targeting cell-free hemoglobin-mediated oxidative stress is warranted.